Engineering of NADPH Supply Boosts Photosynthesis-Driven Biotransformations - Assil-Companioni L; Büchsenschütz HC; Solymosi D; Dyczmons-Nowaczyk NG; Bauer KKF; Wallner S; Macheroux P; Allahverdiyeva Y; Nowaczyk MM; Kourist R (American Chemical Society, 2022)
was reached, allowing the complete conversion of a 60 mM substrate solution within 4 h.